Formation of the synaptonemal complex in a gynogenetic allodiploid hybrid fish - Wang, Jing; Wang, Wen; Li, Jihong; Zhang, Yirui; Luo, Kaikun; Han, Linmei; Xiang, Caixia; Chai, Mingli; Luo, Ziye; Zhao, Rurong; Liu, Shaojun (Frontiers in Genetics, 2023)
The correct pairing and separation of homologous chromosomes during meiosis is crucial to ensure both genetic stability and genetic diversity within species. In allodiploid organisms, synapsis often fails, leading to sterility. However, a gynogenetic allodiploid hybrid clone line (GDH), derived by crossing red crucian carp (Carassius auratus ♀) and common carp (Cyprinus carpio ♂), stably produces diploid eggs. Because the GDH line carries two sets of interspecific chromosomes, it is interesting to study the mechanisms of homologous chromosome pairing during meiosis in GDH individuals. To explore chromosome synapsis in the GDH germ cell during meiosis, we used fluorescence in situ hybridization (FISH) with probe specific to the red crucian carp to label homologous chromosomes, and we identified the synaptonemal complex via the immunofluorescent labeling of synaptonemal complex protein 3 (SCP3). FISH indicated that, during early ovarian development, the GDH oogonia had two sets of chromosomes, only one of which was from Carassius auratus, and that meiosis was blocked because a normal bivalent could not be formed. This developmental stage lasted at least 5 months. After this long period of inhibition, pairs of germ cells fused, doubling the chromosomes such that the oocyte contained two sets of chromosomes from each parent. After chromosome doubling at 10 months old, homologous chromosomes and the synaptonemal complex were identified. From this point, meiosis proceeded normally, as homologous chromosomes could pair, eventually leading to the production of diploid germ cells. These results provide help to clarify the mechanisms by which unreduced gametes are formed in hybrids.